2012
DOI: 10.1080/08927014.2012.687048
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of medetomidine on photosynthesis and protein synthesis in periphyton, epipsammon and plankton communities in relation to predicted environmental concentrations

Abstract: Medetomidine is a new antifouling substance, highly effective against barnacles. As part of a thorough ecotoxicological evaluation of medetomidine, its short-term effects on algal and bacterial communities were investigated and environmental concentrations were predicted with the MAMPEC model. Photosynthesis and bacterial protein synthesis for three marine communities, viz. periphyton, epipsammon and plankton were used as effect indicators, and compared with the predicted environmental concentrations (PECs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This supports the evidence for medetomidine having a high surface affinity and a preference for adsorption [7]. A degradation half-life of 110 d for medetomidine has been used for calculating the PECs for this substance [19].…”
Section: Medetomidine Toxicitysupporting
confidence: 78%
See 2 more Smart Citations
“…This supports the evidence for medetomidine having a high surface affinity and a preference for adsorption [7]. A degradation half-life of 110 d for medetomidine has been used for calculating the PECs for this substance [19].…”
Section: Medetomidine Toxicitysupporting
confidence: 78%
“…In another study, a significant decrease in photosynthetic activity of a plankton community was observed after exposure to 2 mg/L medetomidine . All these toxic effects are considered to be well above the highest predicted environmental water concentrations (PEC water ) for medetomidine of 57 ng/L (PEC derived for a Baltic marina scenario) . In addition to the relatively low toxicity of medetomidine, some of the observed behavioral effects of medetomidine to invertebrates have been shown to be reversible when the animals are removed to clean water .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For medetomidine, Wendt et al (2013) concluded that this antifoulant poses a low risk to the macroalgae Ulva lactuta because the maximum predicted environmental concentration (PEC) is low (0.057 µg l -1 , Ohlauson et al 2012). Conversely, the EC10 for egg production of the copepod A. tonsa was reported as 0.16 µg l -1 (Wendt et al 2016), suggesting that medetomidine might pose a risk to the marine environment, depending on the exposure conditions.…”
Section: Implications For Environmental Risk Assessment (Era)mentioning
confidence: 99%
“…Effectiveness and impact of a variety of antifouling agents were tested. Exposure of algae and bacteria to Medetomidine, a new antifouling substance useful against barnacles, did not result in acute toxic effects on bacterial protein synthesis and resulted in only small acute effects on photosynthesis activity of algae but only at concentrations that would be much higher than predicted environmental concentrations(Ohlauson et al, 2012). After two weeks of immersion, biofilms present on polystyrene, teflon and four antifouling paints were analyzed for the composition and abundance of marine bacterial and diatom assemblages(Briand et al, 2012).…”
mentioning
confidence: 99%